Walter Kasper, La doctrina de la tradición en la Escuela Romana. Sal Terrae: Santander, 201 8, 658 pp. - Mauti, Ricardo M. (2021)
Fil: Mauti, Ricardo M. Pontificia Universidad Católica Argentina, Facultad de Teología; Argentina